2007
DOI: 10.1080/15622970600960157
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia-induced seizure during carbamazepine treatment

Abstract: We report the case of a 54-year-old woman who was admitted for benzodiazepine withdrawal. After 6 weeks of carbamazepine treatment (600, then 200 mg) the patient suddenly suffered from a grand mal seizure. Laboratory findings revealed a clinical significant hyponatremia of Na 125 mmol/l (baseline: 143 mmol/l). CCT and ECG were normal. To our knowledge, this is the first description of a seizure related to hyponatremia in an adult carbamazepine-treated patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…[8] A previous study has also reported a case of a 52-year-old female patient who presented with grand mal epilepsy as a consequence of hyponatremia due to carbamazepine. [9] Other anticonvulsants causing hyponatremia are oxcarbamazepine and lamotrigine. All these drugs alter the vasopressin levels in the renal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…[8] A previous study has also reported a case of a 52-year-old female patient who presented with grand mal epilepsy as a consequence of hyponatremia due to carbamazepine. [9] Other anticonvulsants causing hyponatremia are oxcarbamazepine and lamotrigine. All these drugs alter the vasopressin levels in the renal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Grand-mal seizure related to hyponatremia (Na 125 mEq/L) in a 54-year-old woman after six weeks of carbamazepine treatment has been reported. [4] Possible mechanisms for the antidiuretic effects of carbamazepine include alteration in sensitivity or set-point ofhypothalamic osmoreceptors or increased sensitivity of the renal tubules to circulating anti-diuretic hormone. [4] Carbamazepine can induce kidney water absorption by increasing aquaporin-2 expression in inner medullary collecting ducts.…”
Section: Discussionmentioning
confidence: 99%
“…An ADR is considered severe if, -it is (potentially) life-threatening or seriously endangers a patient's health, -it causes considerable impairment of everyday functioning, or -it makes a transfer to another ward or department necessary for more specialized care (Grohmann et al 2004(Grohmann et al , 2014.…”
Section: Methodsmentioning
confidence: 99%
“…The AMSP protocol provides additional guidelines based on each organ system to further standardize classification (Grohmann et al 2014).…”
Section: Methodsmentioning
confidence: 99%